2008
DOI: 10.1007/s10719-008-9170-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycomic profiling of invasive and non-invasive breast cancer cells

Abstract: Quantitative profiling of glycans with different structures appears essential for a better understanding of the cellular adhesion phenomena associated with malignant transformation and the underlying aberrant glycosylation of cancer cells. Using the recently developed glycomic techniques and mass-spectrometric measurements, we compare the N-linked and O-linked oligosaccharide profiles for different breast cancer cell lines with those of normal epithelial cells. Statistically significant differences in certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 29 publications
6
70
0
2
Order By: Relevance
“…Very similar pattern and significant decrease in sialylation and fucosylation in breast cancer cell lines was recently reported by Goetz at al. 50 In our study, the largest glycans was observed at m/z 3997.4 and its composition corresponded to a tetra-antennary core fucosylated structure with bisecting moiety and NeuAc residues on each antenna (Figure 2a, Table 1). Due to low intensity, CID spectra of sialylated glycans were noisier than others discussed above, however the signal was sufficient for structural investigation.…”
Section: Maldi-ms Analysis Of N-glycans From Mcf-7 and Cemsupporting
confidence: 49%
“…Very similar pattern and significant decrease in sialylation and fucosylation in breast cancer cell lines was recently reported by Goetz at al. 50 In our study, the largest glycans was observed at m/z 3997.4 and its composition corresponded to a tetra-antennary core fucosylated structure with bisecting moiety and NeuAc residues on each antenna (Figure 2a, Table 1). Due to low intensity, CID spectra of sialylated glycans were noisier than others discussed above, however the signal was sufficient for structural investigation.…”
Section: Maldi-ms Analysis Of N-glycans From Mcf-7 and Cemsupporting
confidence: 49%
“…A similar study involving cytosolic glycoproteins from breast cancer cell lines also showed that high mannose N-glycans were significantly elevated in invasive and noninvasive breast cancer cells as compared with the normal breast epithelial cells (83). Although it remains unclear whether high mannose glycans are a common feature of most cultured cell lines, the presence of high mannose structures reported here correlates with the study by Jacob et al (2012) who showed that naturally occurring anti-glycan antibodies such as anti-Man, present in ovarian cancer patients' plasma exhibited specific binding of high mannose structures using a printed glycan-array technology (23).…”
Section: Gene Expression Of Specific Glycosyltransferases In Ovarian mentioning
confidence: 68%
“…For example, Man 5 -Man 7 glycans were present in mice implanted with head and neck tumor but not in healthy mice (29). In a different study, Man 5 -Man 8 glycans were statistically elevated in the soluble cytosolic glycoproteins isolated from invasive and noninvasive breast cancer cells compared with those isolated from normal epithelial cells (32). Another report (33) shows high mannose oligosaccharides to be more prevalent in the cell surface of tumor cells compared with normal cells.…”
Section: Distinct Differences In N-linked Glycan Intensities Between mentioning
confidence: 95%